La calidad del servicio y satisfacción del cliente de la empresa San Martin Autopartes Empresa Individual de Responsabilidad Limitada agosto 2024 - Del Águila Miranda, Ingrid Melissa (2025)
Service quality and customer satisfaction are fundamental to the success of any company. These variables are interrelated and have a direct impact on various aspects of the business: such as customer retention, reputation and recommendation, increased income, reduction of complaints and costs, competitive advantage and continuous improvement, therefore the research aimed to determine the relationship that exists between Service Quality and Customer Satisfaction of the company San Martín Autopartes Individual Company of Limited Liability August 2024, using a non-experimental, descriptive, correlational, cross-sectional quantitative approach; The sample was made up of 45 clients of the company and the results show that there is a positive and significant correlation between the Service Quality variable and the Customer Satisfaction variable with a Pearson correlation coefficient of 0.468, moderate magnitude and a bilateral significance of 0.001 whose interpretation tells us that as one variable increases, the other also tends to increase, but not in a perfectly linear way.